2016
DOI: 10.14569/ijacsa.2016.070416
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Text Hiding in the Image by Using LSB

Abstract: Abstract-an important topic in the exchange of confidential messages over the internet is the security of information conveyance. For instance, the producers and consumers of digital products are keen to know that their products are authentic and can be differentiated from those that are invalid .The science of encryption is the art of embedding data in audio files, images, videos or content in a way that would meet the above security needs. Steganography is a branch of data-hiding science which aims to reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In 2016, R. Tavoli, et al have suggested a new method for image steganography using LSB‫و‬ Where the proposal first includes compressing text data before hiding the data in the image and is encoded by using a 4 * 4 mask called snake scan order, after implemented compressed and snake scan order then loaded text in the image for embedding and extracting the used key and without key when the length of the key is dynamic, Then the researcher suggested making XOR the key and text after converting them into binary and the output is coding, then the result code applies XOR with the key and decode is produced. The result of the proposed method is illustrated measurements PSNR and MSE in each (RGB) channel which is the result of peak-signal-to-noise Ratio between (51.78-58.81) and the result of Mean Square Error between (0.1087-0.4363) when using Lena image and another image [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In 2016, R. Tavoli, et al have suggested a new method for image steganography using LSB‫و‬ Where the proposal first includes compressing text data before hiding the data in the image and is encoded by using a 4 * 4 mask called snake scan order, after implemented compressed and snake scan order then loaded text in the image for embedding and extracting the used key and without key when the length of the key is dynamic, Then the researcher suggested making XOR the key and text after converting them into binary and the output is coding, then the result code applies XOR with the key and decode is produced. The result of the proposed method is illustrated measurements PSNR and MSE in each (RGB) channel which is the result of peak-signal-to-noise Ratio between (51.78-58.81) and the result of Mean Square Error between (0.1087-0.4363) when using Lena image and another image [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The save (s 1 ) and carry (c 1 ) from the summation in CSA1 are further computed using CPA3 to obtain the third MRD, ϑ 3 in Equation 12. Equations (17) and (18) are obtained by a concatenation process requiring no hardware, and finally the results of Equations (18) and (19) are computed using CPA4 in order to get the binary number X as in Equation 20. The area complexity of this architecture is (7n−4) FA comprising of three (n − 1)-bits full adders (i.e.…”
Section: B Implementation Of the Proposed Schemementioning
confidence: 99%
“…In [17], a scheme was proposed that combined a number of algorithms including AES, a hybrid of Discrete Wavelet Transform and Discrete Cosine Transform watermarking techniques and RNS for image security. A scheme by [18] used the Least Significant Bit technique to hide texts in images. It investigated the multiple approaches of steganography for images, and argued that compression in the frequency domain algorithms are appropriate for effectively hiding text within images without perceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Here, system date and time is taken to generate the password for each instance and then positions of the characters of the password are randomly changed to finalize the ultimate password which is chosen as confidential information. This confidential information is embedded into a cover image [10] using a unique embedding technique based on the exact length of bits in the binary representation of ASCII [11] values. This needs minimal modification at LSB of the cover image and assures space saving over the existing LSB technique.…”
Section: The Proposed Solutionmentioning
confidence: 99%